**DERIVING THE QUADRATIC FORMULA**

## ax^{2} + bx + c = 0

Subtract c from both sides of the equation.

## ax^{2} + bx = -c

Divide both sides by the coefficient of x^{2}.

## x^{2} + (b/a)x = -c/a

Divide the coefficient of x by 2, square it, then add to both sides.

Note: This makes a perfect square on the left side.

## x^{2} + (b/a)x + b^{2}/4a^{2} = -c/a + b^{2}/4a^{2}

Simplify the left side into a square.

## (x + b/2a)^{2} = -c/a + b^{2}/4a^{2}

Simplify the right side by finding the lowest common denominator.

## (x + b/2a)^{2} = -4ac/4a^{2} + b^{2}/4a^{2}

Add the fractions on the right.

## (x + b/2a)^{2} = (b^{2} - 4ac)/4a^{2}

Take the square root of both sides.

Note: The term +/-sqrt = plus or minus the square root of.

## x + b/2a = +/-sqrt(b^{2} - 4ac)/2a

Subtract b/2a from both sides and simplify.

## x = [-b +/-sqrt(b^{2} - 4ac)]/2a

Do you understand my child?

**AN EXAMPLE USING THE QUADRATIC FORMULA**

If...

2x^{2} + 3x + 22 = 49

Then...

2x^{2} + 3x + (-27) = 0

Using the quadratic formula...

x = [-3 +/-sqrt(3^{2} - 4(2)(-27))]/[2(2)]

x = [-3 +/-sqrt(225)]/4

x = -3/4 +/-(15/4)

Therefore...

x = 3 or x = -4.5

PRINTER FRIENDLY

This tutorial created and designed by

Curtis Lee Hall

www.InTheBeginning.com

This webpage is dedicated to

Jodi

The Great Mathematician of Bates Hollow.

Truly a very precious spirit, a brilliant and beautiful soul.

(1Peter 3:4)

Intriguing -
(adjective) causing a desire to know more; mysterious.

There is a River

by Mike De Lorenzo

My Father's House Ministries

Used by permission

OnlineConversion.com

Convert just about anything to anything else.

631